Prevención de Caídas: ¡Reduzca su riesgo! - Jennifer Hillan; Linda B. Bobroff (EDIS)
Revised! FCS2231-Span, a 1-page handout by Jennifer Hillan and Linda B. Bobroff, is the Spanish language version of FCS2231/FY737: Fall Prevention: Reduce Your Risk! which tests knowledge of lifestyle factors that can affect the risk of falling using a simple crossword puzzle activity. Published by the UF Department of Family Youth and Community Sciences, August 2010.